How Does Emotional Appetite and Depression Affect BMI and Food Consumption? - Öngün Yılmaz, Hande; Köse, Gizem (Progress in Nutrition, 2021)
Objective: In this study, it was aimed to examine the relationship between body mass index (BMI) and food consumption by demonstrating emotional appetite and depression in young adults. Methods: This study carried out with 1324 university students whose mean age was 21.01±2.19 in Turkey. Food consumption records, Emotional Appetite Questionnaire (EMAQ), and Beck Depression Inventory (BDI) were used. Results: Participants’ mean daily energy intake was 2026.69±724.86 calories, and the consumption of males was higher (p < .001). Males had higher EMAQ-P score than females (p < .05). EMAQ-N, EMAQ-NE, and BDI scores were the highest in the obese group (p < .05). A negative correlation was found between BDI and EMAQ-N (r = - .067, p < .05), also a positive correlation between BMI and EMAQ-N (r = .124, p < .01). Energy consumption and EMAQ-N (r = .070, p < .05), EMAQ-P (r = .060, p < .05) and BMI (r = .106, p < .01) were correlated. Conclusion: Detecting and recognizing emotional appetite at a young age can help cope with appetite in adulthood and older ages. More studies are needed to reveal the effects of mood and emotional states of young adults on food consumption, food preferences, and body composition.